2021
DOI: 10.1590/1413-81232021266.11642019
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative evaluation of school meal menus offered in Brazilian municipalities

Abstract: This article aims to evaluate the quality of Brazilian school meal menus. Cross-sectional study that analyzed 2,500 menus of 500 Brazilian municipalities. The menus were evaluated based on the Quality Index for School Meal Menus (IQCAE - Indicador de Qualidade para Cardápios da Alimentação Escolar). The data were submitted to descriptive analysis. We found that 29,4% of menus presented high quality; 50,6%, regular quality; and 20%, low quality. Grains and tubers (86%) and Meat and eggs (67%) were the groups mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
1
0
3
Order By: Relevance
“…Data from other countries also showed that free school meals are positively associated with the quality of students' diet and food security 17 . A Brazilian study assessed 2,500 school meal menus by a quality index that was previously validated and found that only 20% presented low quality 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Data from other countries also showed that free school meals are positively associated with the quality of students' diet and food security 17 . A Brazilian study assessed 2,500 school meal menus by a quality index that was previously validated and found that only 20% presented low quality 18 .…”
Section: Discussionmentioning
confidence: 99%
“…12 No entanto, a inspeção sobre a qualidade do cardápio ainda é precária, tendo em vista os resultados obtidos na avaliação da alimentação escolar brasileira. 13 O desenvolvimento de ferramentas para avaliar a qualidade da alimentação visa auxiliar, de maneira simples e rápida, as atividades do nutricionista, dos conselheiros da alimentação escolar, de gestores públicos e da população em geral. Há disponível na literatura apenas um instrumento para avaliação de cardápios escolares no Brasil, porém não validado.…”
Section: Discussionunclassified
“…A base de dados é composta por dados secundários 2125 cardápios diários que correspondem a 425 cardápios semanais de municípios de todas as regiões do país 1 . Os cardápios foram avaliados com base em 14 componentes (ver Quadro 1), conforme proposto por [Camargo et al 2021…”
Section: Aquisic ¸ãO Dos Dadosunclassified
“…No entanto, tais ac ¸ões são realizadas sob demanda sem que haja um acompanhamento efetivo como, por exemplo, um instrumento de avaliac ¸ão de cardápios escolares que possa contribuir para o monitoramento do PNAE e, consequentemente, melhorar da qualidade das refeic ¸ões. [Camargo et al 2021] propuseram o Índice de Qualidade para Cardápios da Alimentac ¸ão Escolar (IQCAE) para avaliar a qualidade das refeic ¸ões escolares em âmbito nacional, com base na legislac ¸ão vigente, de modo a contribuir para o monitoramento do PNAE [Brasil 2009]. No entanto, a avaliac ¸ão é realizada de forma manual, que pode ser afetada por diversos fatores humanos como fadiga, cansac ¸o e falta de atenc ¸ão.…”
Section: Introduc ¸ãOunclassified